Autorzy:Joanna Czarnowska, Jolanta Wesołowska, Wojciech Babiański, Lech Chańko
Wydawnictwo:Nowa Era
Rok wydania:2014
Zapisz w postaci sumy algebraicznej 4.8 gwiazdek na podstawie 5 opinii

Zapisz w postaci sumy algebraicznej

3Zadanie
4Zadanie
5Zadanie
6Zadanie
7Zadanie
8Zadanie

`a)\ (x+1)(x-1)(x^4+x^2+1)=(x^2-1)(x^4+x^2+1)=(x^2)^3-1^3=x^6-1` 

`b)\ (sqrt5x+1)(sqrt5x-1)(25x^4+5x^2+1)=(5x^2-1)(25x^4+5x^2+1)=(5x^2)^3-1^3=125x^6-1` 

`c)\ (sqrt3-3x^2)(9x^8+3x^4+1)(sqrt3x^2+1)=(1+sqrt3x^2)(1-sqrt3x^2)*sqrt3*(9x^8+3x^4+1)=(1-3x^4)*sqrt3*(9x^8+3x^4+1)=` 

`\ \ \ =(1-3x^4)(1+3x^4+9x^8)*sqrt3=(1^3-(3x^4)^3)*sqrt3=(1-27x^12)*sqrt3=sqrt3-27sqrt3x^12` 

`d)\ (x-1)^2(1+x+x^2+x^3)(x+1)(x^2+1)=(x-1)*ul(ul((x-1)(1+x+x^2+x^3)))(x+1)(x^2+1)=(x-1)(x^4-1)(x+1)(x^2+1)=` 

`\ \ \ =(x-1)(x+1)(x^2+1)(x^4-1)=(x^2-1)(x^2+1)(x^4-1)=(x^4-1)(x^4-1)=(x^4-1)^2=x^8-2x^4+1`